Emergency department environmental contamination with methicillin-resistant Staphylococcus aureus following care of colonized patients - Liang, Stephen Y. (Ann Emerg Med, 2019)
STUDY OBJECTIVE: Methicillin-resistant Staphylococcus aureus (MRSA) transmission dynamics in the emergency department (ED) are not well defined; environmental surfaces may serve as reservoirs for transmission. This study investigated the impact of patients with a history of MRSA colonization or infection on subsequent MRSA contamination of the ED environment. METHODS: Adult ED patients with evidence of an MRSA-positive surveillance or clinical microbiologic culture in the year preceding their current ED visit were enrolled. Cultures from 5 anatomic sites were obtained to detect active MRSA colonization. After patient discharge and prior to environmental disinfection, up to 16 pre-specified surfaces in their ED rooms were cultured. Strain typing was performed by repetitive-sequence PCR on all recovered MRSA isolates to determine concordance with the corresponding patient strain. RESULTS: Of 42 patients enrolled, 25 (60%) remained colonized with MRSA. Nineteen of the 25 (76%) ED rooms occupied by MRSA-colonized patients contained ≥1 MRSA-contaminated environmental surface upon discharge. Surfaces were more likely to be contaminated when rooms were occupied by patients colonized with MRSA at 1 body site (odds ratio [OR], 11.7; 95% CI, 1.5–91.5) and ≥2 body sites (OR, 16.3; 95% CI, 3.1–86.8) compared to non-colonized patients. In 16 of the 19 (84%) ED rooms where MRSA was recovered, all environmental strains were concordant with the corresponding patient strain. CONCLUSION: Contamination of the ED environment with MRSA from actively colonized patients is common. Improved environmental surface disinfection may help reduce transmission of MRSA to ED healthcare professionals and patients during emergency care.